2019
DOI: 10.1039/c9ra06892a
|View full text |Cite
|
Sign up to set email alerts
|

3(2H)-pyridazinone derivatives: a new scaffold for novel plant activators

Abstract: Due to the emergence of drug resistance, pesticide residue and environmental contamination, it is important to develop novel eco-friendly strategies to protect plants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The underlying mechanisms of action are not yet clear (Maienfisch & Edmunds, 2017). Structure-activity relationship studies are conducted with chlorinesubstituted derivatives of SA and fluorine-containing BTH molecules both potent SAR inducers (Conrath et al 1995;Fan et al 2009;Du et al 2011;Chang et al 2017;Shi et al 2019).…”
Section: Thiadiazole Isothiazole and Pyrazole Derivativesmentioning
confidence: 99%
“…The underlying mechanisms of action are not yet clear (Maienfisch & Edmunds, 2017). Structure-activity relationship studies are conducted with chlorinesubstituted derivatives of SA and fluorine-containing BTH molecules both potent SAR inducers (Conrath et al 1995;Fan et al 2009;Du et al 2011;Chang et al 2017;Shi et al 2019).…”
Section: Thiadiazole Isothiazole and Pyrazole Derivativesmentioning
confidence: 99%
“…13 Therefore, SHAFTS (SHApe-FeaTure Similarity) attracts our attention, which is a hybrid 3D similarity calculation method reported by Li et al 14−16 A new scaffold of plant activators has been reported by Shi et al with the application of SHAFTS. 17 We tried to use SHAFTS for the discovery of nematicide lead.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Using Cresset’s software, researchers found the early lead of tioxazafen based on SCA series (stilbenes, chalcones, and azobenzene derivatives) . Therefore, SHAFTS (SHApe-FeaTure Similarity) attracts our attention, which is a hybrid 3D similarity calculation method reported by Li et al A new scaffold of plant activators has been reported by Shi et al with the application of SHAFTS . We tried to use SHAFTS for the discovery of nematicide lead.…”
Section: Introductionmentioning
confidence: 99%